Research Progress on Rapid Detection Technology and Standardized Application of Foodborne Pathogens - Peng WU; Yahe SUN; Xuli ZHU; Shuhua ZHOU; Chengyun ZHANG (Shipin gongye ke-ji, 2024)
In recent years, with the rapid development of new food safety testing technologies, rapid detection of foodborne pathogens has improved traditional detection methods that suffer from long cycles and low sensitivity, thus playing an important role in safeguarding public health and promoting economic and social development. Standardization is the key to the promotion and application of rapid detection technologies. This article systematically introduces commonly used rapid detection methods for foodborne pathogens, including physiological and biochemical detection, immunological detection, and molecular detection. The principles, research progress, advantages, and disadvantages of various methods are summarized. What’s more, domestic and abroad standardization status and application of rapid detection technologies are further introduced from a standardization perspective. The new rapid detection technology has the advantages of sensitivity, speed, and strong specificity, but there are also certain shortcomings, such as the cumbersome pre-treatment of antibodies in immune detection technology, the confusion of contaminated bacteria in physiological and biochemical detection technology, and certain false positives in molecular detection technology. In addition, most detection methods are still illegal and lack unified judgment standards. The relevant standard systems at home and abroad are still incomplete, which restricts the standardized promotion and application of rapid detection technology. Therefore, this article proposes suggestions for the future development of rapid detection technology for foodborne pathogens from the perspective of standardization, in order to provide reference for the research and standardization construction of food safety-related technologies in the future.